2008
DOI: 10.1093/nar/gkn129
|View full text |Cite
|
Sign up to set email alerts
|

Structural probing of the HIV-1 polypurine tract RNA:DNA hybrid using classic nucleic acid ligands

Abstract: The interactions of archetypical nucleic acid ligands with the HIV-1 polypurine tract (PPT) RNA:DNA hybrid, as well as analogous DNA:DNA, RNA:RNA and swapped hybrid substrates, were used to probe structural features of the PPT that contribute to its specific recognition and processing by reverse transcriptase (RT). Results from intercalative and groove-binding ligands indicate that the wild-type PPT hybrid does not contain any strikingly unique groove geometries and/or stacking arrangements that might contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 54 publications
(62 reference statements)
1
36
0
Order By: Relevance
“…This indicates a unique environment at the PPT/U3 junction with even greater stacking rigidity at the +1a site that prevents access of NMIA (analogous to our observations with the À8T/dF hybrid), despite loss of hydrogen-bonding capacity. While the 19 F spectrum and lack of acylation at +1a in the +1dF-substituted hybrid suggests rigidity at this position, the PPT/U3 junction is selectively targeted by the aminoglycoside neomycin B, which has been shown to interact with motifs that disrupt regular double-helical patterns (Turner et al 2008a). Similarly, chemical footprinting indicated that template +1T of the wild-type PPT RNA/DNA hybrid is sensitive to KMnO 4 oxidation, suggesting that the duplex structure at the PPT/U3 junction deviates from canonical Watson-Crick geometry.…”
Section: Nmia Sensitivity Of Analog-substituted Hiv-1 Pptsmentioning
confidence: 99%
“…This indicates a unique environment at the PPT/U3 junction with even greater stacking rigidity at the +1a site that prevents access of NMIA (analogous to our observations with the À8T/dF hybrid), despite loss of hydrogen-bonding capacity. While the 19 F spectrum and lack of acylation at +1a in the +1dF-substituted hybrid suggests rigidity at this position, the PPT/U3 junction is selectively targeted by the aminoglycoside neomycin B, which has been shown to interact with motifs that disrupt regular double-helical patterns (Turner et al 2008a). Similarly, chemical footprinting indicated that template +1T of the wild-type PPT RNA/DNA hybrid is sensitive to KMnO 4 oxidation, suggesting that the duplex structure at the PPT/U3 junction deviates from canonical Watson-Crick geometry.…”
Section: Nmia Sensitivity Of Analog-substituted Hiv-1 Pptsmentioning
confidence: 99%
“…In this direction, we have employed sustained off-resonance irradiation (SORI) 24 CID to characterize the unique structural features exhibited by DNA-RNA hybrid duplexes 25, 26 and RNA stemloop structures 27, 28 involved in viral replication. The observation that backbone fragmentation could be inhibited by the contact of non-covalent ligands 27 prompted us to propose the utilization of classic nucleic acid ligands as non-covalent structural probes.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, competitive binding experiments in which multiple ligands are mixed simultaneously with the substrate of interest have proven very effective in providing relative scales of binding affinities based on the aspect ratio and distribution of the detected complexes [130 -133]. Reversing the terms of the competition scheme, a ligand of interest can be also added to multiple substrates simultaneously, for example, to directly compare the effects of subtle variations in substrate structure on binding mode ( Figure 5) [134]. In more rigorous fashion, quantitative determinations of K d can be accomplished by following titration schemes in which the amount of ligand is increased stepwise and the abundances of free/bound species in solution are determined after each addition [125][126][127][128].…”
Section: Elucidating Structure-function Relationshipsmentioning
confidence: 99%
“…Under suitable activation conditions, the binding of selected ligands to RNA substrates can prevent underlying nucleotides from undergoing the typical backbone fragmentation that produces the characteristic ion series employed in MS/MS sequencing. This observation has promoted strategies for achieving the characterization of specific binding sites onto target nucleic acid structures, which are revealed by recognizable gaps in the detected ion series [134,171,172]. Conversely, the same protection effects can be employed to screen libraries of small molecule ligands for their ability to bind to desired structural motifs, which is evaluated from their power to induce sitedirected inhibition of nucleic acid fragmentation [123,173].…”
Section: Elucidating Structure-function Relationshipsmentioning
confidence: 99%